COMPETITIVE POSITION OF POLISH SUGAR SECTOR - Klepacki, Bogdan; Klimczuk, Bogusław (Acta Scientiarum Polonorum. Oeconomia, 2003)
In the paper the competition of Polish sugar industry has been presented. The authors have pointed that the sector is very concentrated. There are rather no possibilities to set up new sugar factories next few years. Sugar companies with foreign capital have better competitive position than Polish firms.